Fish-for-Sex (FFS) and risk of HIV Infection among Fishers in Elmina Fishing Community in Ghana - Kyei-Gyamfi, Sylvester (African Human Mobility Review, 2022)
This paper is a follow-up to a cross-sectional study which employed mix-methods for data collection and analysis to investigate a relationship between mobility and HIV risks amongst 385 fishers in Elmina. It discusses the roles of men and women in fish-for-sex (FFS), reasons for such transactional sexual activity and its implications for HIV risk infection. The theory of gender and power has been utilized to explain gender dynamics in power inequalities, and their effects on interpersonal sexual relationships between males and females within the fishing community.  The paper concludes sex-division of labour exists in the study area and thrives on socio-cultural norms and power inequalities, which mainly favours men, as it gives them the power to exploit women through the supply of fish.  Another observation from the paper is that as long as the female fishers require capital for their fish trade and the male fishers have greater control over the supply of the fish, the women will have very little basis to negotiate for.  The paper therefore establishes linkage between fish-for-sex relationship and risk of HIV exposure among fishers in Elmina. The paper recommends empowerment of female fishers by granting them trading capital to limit their overdependence on male fishers for capital, and prevent them from exchanging sex for fish. The paper also calls for the intensification of education by relevant agencies involved in HIV education on safe sex practices through the use of condoms in fishing communities.